Cannabis use and co‐use in tobacco smokers and non‐smokers: prevalence and associations with mental health in a cross‐sectional, nationally representative sample of adults in Great Britain, 2020. (22nd January 2021) - Hindocha, Chandni; Brose, Leonie S.; Walsh, Hannah; Cheeseman, Hazel
Abstract: Background and aims: In Great Britain, cannabis and tobacco are commonly used substances, both independently and together. Use of either substance is associated with mental health problems, but prevalence of co‐use within these populations is unknown. We aimed to (1) estimate prevalence of cannabis use, frequency of use and routes of administration (ROA) among tobacco smokers and non‐smokers and (2) investigate mental health problems among non‐users, tobacco‐only, cannabis‐only and co‐users of both substances. Design: Cross‐sectional national on‐line survey (Action on Smoking and Health) fielded in February–March 2020. Setting: Great Britain. Participants: Adults in Great Britain aged ≥ 18 years ( n = 12 809) Measurements: Tobacco use status [smoker (daily or non‐daily) or non‐smoker (never or ex‐smoker)], cannabis use frequency (never to daily), detailed ROAs of cannabis, self‐reported treatment for mental health disorders (depression, anxiety and any). Statistically weighted prevalence estimates were computed to ensure representativeness. Correlates were assessed using χ 2 tests and logistic regression. Findings: In Great Britain in 2020, 7.1% of the sample had used cannabis in the past year. Tobacco smokers had greater odds of using cannabis in the past year (21.9%) and using cannabis daily (8.7%) than non‐smokers [past‐year: 4.7%; adjusted odds ratio (aOR) = 10.07, 95% confidence interval (CI) = 8.4–12.0; daily: 0.7%; aOR = 24.6, 95% CI = 18.0–33.6)]. Co‐administration with tobacco was common (46.2% of non‐smokers, 80.8% of tobacco smokers). Co‐users reported the highest prevalence of any treatment for mental health problems (54.2%) in comparison to cannabis‐only (45.8%), tobacco‐only (33.2%) and non‐users (22.7%; all P ≤ 0.05). Conclusion: Approximately one in 13 adults in Great Britain reports having used cannabis in the past year, approximately four times as many among cigarette smokers as non‐smokers. Co‐administration of cannabis and tobacco, via smoking, appears to be common, including among self‐identified non‐smokers. Mental health problems appear to be particularly common among dual users.